2004
DOI: 10.1093/annonc/mdh315
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of the farnesyl transferase inhibitor R115777 in patients with sensitive relapse small-cell lung cancer

Abstract: R115777 showed no significant antitumor activity as a single agent in sensitive-relapse SCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…R115777 was administered in 3-week cycles at a dose of 400 mg orally twice daily for 14 consecutive days followed by seven days off treatment, and 22 patients were enrolled. The trial was terminated as no objective responses were observed in the 20 patients evaluable for response (59). was closely associated with the induction of immunological response to vaccination.…”
Section: Other Agentsmentioning
confidence: 99%
“…R115777 was administered in 3-week cycles at a dose of 400 mg orally twice daily for 14 consecutive days followed by seven days off treatment, and 22 patients were enrolled. The trial was terminated as no objective responses were observed in the 20 patients evaluable for response (59). was closely associated with the induction of immunological response to vaccination.…”
Section: Other Agentsmentioning
confidence: 99%
“…More recent phase II studies explored higher dosages with strict dose-reduction rules for toxicity. In one study, patients with relapsed small-cell lung cancer received 400 mg twice daily for 14 consecutive days followed by 1 week of rest, and no objective responses and only one case of stable disease were observed [86]. To date, the most promising activity of tipifarnib was reported in patients with untreated poor-risk acute myeloid leukemia or myelodysplastic syndrome (MDS), in which a 33% response rate (eight complete responses, two partial responses) was seen [87].…”
Section: Tipifarnibmentioning
confidence: 99%
“…Farnesyl transferase inhibitors have shown efficacy in preclinical models of SCLC, presumably through effects on the large number of farnesylated second messengers that regulate growth and survival [30]. This observation has not yet successfully translated into the clinic; in an initial phase II clinical trial of 22 patients with relapsed SCLC, the farnesyl transferase inhibitor tipifarnib (Zarnestra ™ , R115777) failed to show clinical activity as a single agent [31].…”
Section: Farnesylation and Receptor-associated Second Messengersmentioning
confidence: 99%